2020
DOI: 10.1002/ieam.4265
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Postdisaster Impact Assessment: A Case Study of the Impacts of the Fundão Dam Failure on Terrestrial Species Threatened with Extinction

Abstract: The Fundão tailings dam held back approximately 50 million cubic meters of tailings from an Fe ore mine in the state of Minas Gerais, Brazil. The dam failed on 5 November 2015, releasing tailings into the Rio Doce watershed and causing an environmental disaster in a biodiversity hotspot. To guide conservation action following the event, Brazilian authorities demanded an impact assessment focused on terrestrial species threatened by extinction. Postdisaster impact assessment is substantially more challenging th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, more studies need to be developed along the Doce River watershed, to better understand its plant diversity and community changes along the river. In the area affected by the collapse of the Fundão dam, 166 threatened species were described (Knopff et al 2020), which is not a surprising number, since this catastrophe affected one of the world's biodiversity hotspots that is extremely endangered. The possibility of high turnover rates of plant species composition along the Doce River from its origin to its end at the Atlantic Ocean represents information of major relevance to the ecological restoration of biodiversity and ecosystem services in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more studies need to be developed along the Doce River watershed, to better understand its plant diversity and community changes along the river. In the area affected by the collapse of the Fundão dam, 166 threatened species were described (Knopff et al 2020), which is not a surprising number, since this catastrophe affected one of the world's biodiversity hotspots that is extremely endangered. The possibility of high turnover rates of plant species composition along the Doce River from its origin to its end at the Atlantic Ocean represents information of major relevance to the ecological restoration of biodiversity and ecosystem services in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Protected natural areas depend, to a large extent, on the sensitivity of national, autonomous and local governments, and can be of very varied typology, such as national parks, natural parks, areas of special interest, special conservation areas, etc. [42]. For the determination of the map with the impact of special ecosystems (Figure 3b), a classification of the entire territory into three different groups is proposed: the protection areas themselves, the buffer zone at 500 m and the rest of the territory.…”
Section: Map Of Special Ecosystems Impactmentioning
confidence: 99%
“…A review of historical tailings dam failures has revealed two distinct mechanisms in which the strain softening behaviour of the material plays a pivotal role. The first mechanism pertains to the progressive development of failure in a weak soil layer within the dam foundation [ 20 , 21 ]. The second mechanism is associated with the static or dynamic liquefaction of loose tailings material at a critical state [ 22 ].…”
Section: Introductionmentioning
confidence: 99%